Sistem Pembinaan Karakter Santriwati di Pondok Pesantren Al-Amanah Liabuku Kota Bau-Bau - Yin Dirman; Bunyamin, Andi; Nashiruddin Pilo (Program Pascasarjana Universitas Muslim Indonesia, 2023)
Liabuku Islamic Boarding School, Bau-Bau City. This research uses qualitative research with a case study approach. The methods used in collecting data are the method of observation, the interview method, and the method of documentation. The collected data was then analyzed using qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and data verification. The findings of researchers in the field related to the strategy of developing the character of female students at the Al-Amanah Liabuku Islamic Boarding School in Bau-Bau City include: internalizing character building through the learning curriculum, extracurricular activities, culture, discipline, and habituation of the students with the values contained in it. It contains the following characteristics: religious, disciplined, independent, responsible, hard work, cooperation/mutual assistance, communication, nationalist, and integrity. Meanwhile, the effectiveness of character building for female students at the Al-Amanah Liabuku Islamic Boarding School in Bau-Bau City is said to have been carried out well and very effectively. This is evidenced by the changes in character that students go through from before entering the pesantren to the years of tasting education in the pesantren environment.